Efeito da taxa de reforço e da concentração de açúcar na preferência por alimentos de composição tradicional ou light em universitários - Macedo, Marina Zanoni (Universidade Federal de São Carlos, 2015)
Food with high sugar concentration exhibits relation with impulsive eating behavior and obesity. This research investigated the effect of different rates of reinforcement and compositions of food, traditional or light, on the choice responses pattern of four undergraduate students. Those foods have similar organoleptic characteristics and different sugar concentration. One study, whith three phases was did, in all of them, two stimuli representing the initial links of a chain-concurrent schedule were presented, simultaneously, to the participants in a computer screen. Choice response in the initial links was followed by the second link of the chain-concurrent schedule. In Phase 1, response in FR1 on the second link was followed by the delivering, in both alternatives, of juice samples with the same composition, flavor and magnitude, an inter-trial interval and another trial. In Phase 2, response in FR1 on the second link was followed by the delivering of samples of traditional juice composition on one terminal link of the chain-concurrent schedule or light juice composition on another terminal link of the chain-concurrent schedule, an inter-trial interval and another trial. In Phase 3, was added primarily contextual stimuli consistent with the structural arrangement indicating which composition would have the juice samples available for each alternative and later this contextual stimuli became inconsistent with the structural arrangement. The sessions presented varied in time. The maximum duration was 10 minutes and occurred, on average, three times a week. The results showed that human subjects have difficult to exhibit maximization in chain-concurrent schedule, have good sensitivity to the different reinforcement rates in chain-concurrent schedule and concentrations of sugar in samples of traditional and light juices composition.
Keywords: Behaviorismo (Psicologia); Lei da igualação; Esquema de reforçamento; Alimentos; Alimentos light; Sobrepeso; Matching law; Chain-concurrent schedules of reinforcement; Traditional food; Light food; Overweight; CIENCIAS HUMANAS::PSICOLOGIA